PENGARUH KONSENTRASI AIR CUCIAN BERAS TERHADAP PERTUMBUHAN PAK CHOI (Brassica rapa L.) DENGAN TEKNIK HIDROPONIK SISTEM WICK SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATERI BIOTEKNOLOGI KELAS XII SMA - Sheliana, Yolanda; Mahadi, Imam; Sayuti, Irda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted to determine the effect of rice washing water concentration on the growth of pak choi (Brassica rapa L.) with wick system hydroponics technique and the design of student worksheet (LKPD) of senior high school grade XII biotechnology materials in February-March 2018. This research carried out in two stages; they are the experimental stage: the effect of the concentration of rice washing water on pak choi growth and the designing stage of the LKPD: the analysis of the potential development of senior high school grade XII biotechnology material for teaching. The research used the experimental method by conducting experiments in the Greenhouse of the Nature Laboratory Biology Education Study Program FKIP Pekanbaru Riau University. Sampling was carried out with a completely randomized design (CRD) consisting of 5 treatments and 3 replications. The parameters in this research were plant height, leaf width, leaf number, root length, and plant dry weight. Based on the results of Analysis of variance (Anava) at the level of 5%, the administration of rice washing water concentration showed a significant effect on the growth of pak choi (Brassica rapa L.). The provision of rice washing water with a concentration of 1 kg of rice with 1 liter of water showed the best growth of the pak choi (Brassica rapa L.) plant and based on the analysis of the research results, it can be used as a draft students worksheet (LKPD) of senior high school grade XII biotechnology materials.Keywords: Rice Washing Water, Pak Choi, Wick System, LKPD Design